Emerging Ethical Issues in Reproductive Medicine: Are Bioethics Educators Ready?. (September 2014) - Farrell, Ruth M.; Metcalfe, Jonathan S.; McGowan, Michelle L.; Weise, Kathryn L.; Agatisa, Patricia K.; Berg, Jessica
Abstract Advocates for the professionalization of clinical bioethics argue that bioethics professionals play an important role in contemporary medicine and patient care, especially when addressing complex ethical questions that arise in the delivery of reproductive medicine. For bioethics consultants to serve effectively, they need adequate training in the medical and ethical issues that patients and clinicians will face, and they need skills to facilitate effective dialog among all parties. Because clinical ethics consultation is a "high‐stakes endeavor" that can acutely affect patient care, efforts are under way to ensure that bioethics consultants have the competence to provide such guidance. Yet to date, no studies have examined whether the training of bioethics consultants meets the needs of health care professionals who are on the front lines of such issues. In fact, limited information is available on the reproductive health issues that bioethics training programs address or the degree to which these programs meet the needs of patients confronting reproductive health decisions and their clinicians. It is therefore important to answer this key question: What are the primary ethical issues encountered in reproductive medicine that currently affect patient care? Equally important, are bioethics training programs prepared to address those issues? To begin to answer these questions, we conducted parallel surveys of directors of graduate bioethics training programs and obstetrician‐gynecologists. The goal of this project is to lay the groundwork to establish a working partnership between bioethics educators and reproductive medicine practitioners to address the often troubling and frequently complex ethical issues in reproductive medicine.